Enhancing sexuality : a problem-solving approach to treating dysfunction : therapist guide - Wincze, John P., 1943- (Treatments that work., 2009)
Sexual dysfunction can cause significant distress in both men and women and their partners. This therapist guide presents a comprehensive program for assessing and treating sexual dysfunction in couples or single individuals, regardless of sexual preference. It outlines pathways for therapy and gives recommendations for formulating a treatment plan. Therapists are encouraged to be flexible in their approach while guiding clients through this step-by-step program. The guide and corresponding workbook present information on a number of sexual problems including low sexual desire, difficulty beco.